Pediatric Digestive Surgery - Lima, Mario (Springer International Publishing : Imprint: Springer, 2017)
This book presents and explains the latest developments in surgery for congenital digestive tract malformations, tumors, abdominal trauma, and the most important acquired digestive disorders. Particular attention is paid to minimally invasive and innovative techniques. In addition to clear descriptions of the surgical procedures that highlight useful tips and tricks, for each condition the clinical presentation is well illustrated and information is provided on pathogenesis. The book also includes general chapters that address the anatomy of the abdomen in children, diagnostic issues, the problem of clinical nutrition, and other aspects of management in pediatric patients with gastrointestinal pathologies. Pediatric Digestive Surgery will serve as a comprehensive and up-to-date reference for all pediatric surgeons. It will provide the trainee with easily understood, concise guidance while offering the more experienced surgeon valuable updates on the latest thinking and practice in the field.
Keywords: Medicine.; Abdominal surgery.; Minimally invasive surgery.; Pediatric surgery.; elektronické knihy; electronic books